2015
DOI: 10.1111/jvh.12484
|View full text |Cite
|
Sign up to set email alerts
|

Reduced healthcare utilization following successful hepatitis C virus treatment in HIV‐co‐infected patients with mild liver disease

Abstract: SummaryNew direct‐acting antivirals (DAA) for hepatitis C virus (HCV) infection have achieved high cure rates in many patient groups previously considered difficult‐to‐treat, including those HIV/HCV co‐infected. The high price of these medications is likely to limit access to treatment, at least in the short term. Early treatment priority is likely to be given to those with advanced disease, but a more detailed understanding of the potential benefits in treating those with mild disease is needed. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Comparisons of the number of healthcare encounters by encounter type are summarized in Table 3. Overall, the median number of healthcare encounters throughout treatment was 8 [interquartile range (IQR) [5][6][7][8][9][10][11][12] for those receiving a 12-week treatment regimen as compared to 6 (IQR 4-11) for those on an 8-week treatment regimen (P=0.07). Fewer laboratory visits were utilized in the 8-week group, with an average of 1.6 visits (median=1) as compared to 2.3 visits (median=2) in the 12week group (P=0.04; for comparison of medians) (Figure 2).…”
Section: Characteristics Of Healthcare Encountersmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of the number of healthcare encounters by encounter type are summarized in Table 3. Overall, the median number of healthcare encounters throughout treatment was 8 [interquartile range (IQR) [5][6][7][8][9][10][11][12] for those receiving a 12-week treatment regimen as compared to 6 (IQR 4-11) for those on an 8-week treatment regimen (P=0.07). Fewer laboratory visits were utilized in the 8-week group, with an average of 1.6 visits (median=1) as compared to 2.3 visits (median=2) in the 12week group (P=0.04; for comparison of medians) (Figure 2).…”
Section: Characteristics Of Healthcare Encountersmentioning
confidence: 99%
“…Previous studies have measured the healthcare costs associated with length of treatment, including expenses related to HCV treatment in those dually infected with Human Immunodeficiency Virus (HIV) (9)(10)(11). Shorter treatment times may critically reduce the financial impact on vulnerable patients and allow savings to both payors and hospital systems.…”
Section: Introductionmentioning
confidence: 99%
“…While preventing hepatic decompensation and HCC are the most recognized advantages of treating HCV, a retrospective analysis of HIV/HCV patients with early liver disease between 2004–2013 indicated patients achieving SVR with IFN-based therapy had lower health-care utilization during the following 5 years, suggesting health systems value of treatment aside from prevention of hepatic complications [86]. A modelling study examining liver fibrosis progression in HCV/HIV co-infected MSM, who often have other co-morbid factors modulating fibrosis progression, suggested deferring treatment in persons who had F0–F1 disease until fibrosis had progressed to F2 or beyond would result in an increase in overall liver-related morbidity and mortality [87].…”
Section: Diagnosis Cost and Accessmentioning
confidence: 99%
“…[15][16][17][18] Recent studies, however, have demonstrated the multiple benefits of successful HCV treatment including reduction in risk of mortality and liver-related events as well as reductions in medical expenditures. [19][20][21] Moreover, there is evidence to suggest HIVinfected patients are at increased risk of mortality as compared to HIV negative patients. 6,22 As a result, identifying and addressing modifiable risk factors for renal disease progression and mortality is paramount in this population.…”
Section: Introductionmentioning
confidence: 99%